Mendeteksi Kecurangan Pada Laporan Keuangan Dengan Menggunakan Fraud Triangle - Ataina Rusyda Fauziyah; Shirky Kharisma Fitri Hasnita; Tries Ellia Sandari (Journal of Economic and Business Advancement, 2026)
This study aims to examine the effectiveness of the fraud triangle theory in detecting financial statement fraud. The fraud triangle consists of pressure, opportunity, and rationalization, which collectively explain the behavioral and structural factors behind fraudulent financial reporting. Using a literature-based analytical approach, this study reviews empirical findings from various sectors, including banking, manufacturing, mining, state-owned enterprises, and public institutions. The results indicate that pressure arising from financial targets and performance demands encourages management to manipulate financial information. Opportunity is created through weak internal controls, ineffective monitoring, and complex organizational structures. Rationalization allows perpetrators to justify fraudulent actions as acceptable or temporary solutions. The interaction among these elements significantly increases the likelihood of financial statement fraud. The findings highlight the importance of strengthening corporate governance, internal control systems, ethical culture, and audit quality to reduce fraud risk. This study contributes to the accounting literature by reinforcing the relevance of fraud triangle theory as an analytical framework for fraud detection and prevention in financial reporting.